2016
DOI: 10.1152/ajplung.00289.2015
|View full text |Cite
|
Sign up to set email alerts
|

Systemic interleukin-2 administration improves lung function and modulates chorioamnionitis-induced pulmonary inflammation in the ovine fetus

Abstract: Chorioamnionitis, an inflammatory reaction of the fetal membranes to microbes, is an important cause of preterm birth and associated with inflammation-driven lung injury. However, inflammation in utero overcomes immaturity of the premature lung by inducing surfactant lipids and lung gas volume. Previously, we found that lipopolysaccharide (LPS)-induced chorioamnionitis resulted in pulmonary inflammation with increased effector T cells and decreased regulatory T cell (Treg) numbers. Because Tregs are crucial fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 47 publications
(57 reference statements)
0
28
0
Order By: Relevance
“…Differences are considered statistically significant at p ≤ 0.05. Differences with a p < 0.10 are also taken into account because of the small study groups and because of potential biological relevance, and described as tendencies as previously described (Willems et al 2016 ). This assumption will decrease the chance of a type II error, but increases the chance of a type I error.…”
Section: Methodsmentioning
confidence: 99%
“…Differences are considered statistically significant at p ≤ 0.05. Differences with a p < 0.10 are also taken into account because of the small study groups and because of potential biological relevance, and described as tendencies as previously described (Willems et al 2016 ). This assumption will decrease the chance of a type II error, but increases the chance of a type I error.…”
Section: Methodsmentioning
confidence: 99%
“…Paraffin-embedded RUL tissues were cut (4 μm) and stained for CD3 to identify T cells, for myeloperoxidase (MPO) to detect activated neutrophils and monocytes, and for α-smooth muscle actin (α-SMA) to visualize the tunica media of arterioles [20, 25]. Information about antibodies and protocols were published previously for MPO [26] and CD3 [19].…”
Section: Methodsmentioning
confidence: 99%
“…The levels of IL-2 and Treg-related cytokines in BALF and serum gradually decreased in ALI over time ( 80 ). Animal studies have shown that in chorioamnionitis, systemic treatment with IL-2 expanded Tregs preferentially by increasing the ratio of FoxP3 + /CD3 + in fetal lungs, thus improving lung function and modulating pulmonary inflammation ( 81 ). However, there is little evidence of ARDS/ALI induced by other causes.…”
Section: Tgf-β Il-6 and Il-2mentioning
confidence: 99%
“…There has also been some indirect evidence that Tregs have an impact on TNF-α ( 60 , 61 ), IL-2 ( 81 , 101 ), and IL-8 ( 87 ). In addition, some immunosuppressive molecules [BLT1 ( 20 , 101 ), PD-1 ( 106 ), and CD73 ( 107 )] have also been shown to play an important role in Treg immune function in ALI.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%